In vivo knee biomechanics during badminton lunges at different distances and different foot positions by using the dual fluoroscopic imaging system - Peng, Di; Mao, Zheng; Zhang, Wang; Yu, Jinglun; Zhang, Shengnian (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Lunges are common in badminton. Distance and foot position affect knee joint loadings under lunges, which are closely related to knee injury incidence. Investigations involving dynamic knee motion in vivo, kinetics, and muscle activation in lunges, especially during lunges of different distances and foot positions, are instrumental for understanding knee performance and injury risks of players. Methods: Ten experienced badminton athletes (10 females; height, 164.5 ± 5.0 cm; weight, 59.3 ± 6.0 kg; and age, 22 ± 1.0 years) were recruited. By using a high-speed dual fluoroscopic imaging system, Qualisys motion capture system, Kistler force plate, and Delsys electromyography simultaneously, data were collected during players' 1.5 times leg length lunge, the maximum lunge, and the maximum lunge while the foot rotated externally. Magnetic resonance and dual fluoroscopic imaging techniques were used to analyze the in vivo knee kinematics. Results: Compared with the 1.5 times leg length lunge, knee flexion for the maximum lunge increased significantly (P < 0.05). The anterior-posterior ground reaction force (GRF) and vertical GRF of the maximum lunge were significantly higher than those of the 1.5 times leg length lunge. During the two different foot position lunges with the maximum distance, the posterior translation of knee joint was larger (P < 0.05) when the foot rotated externally than the normal maximum lunge. Moreover, the anterior-posterior GRF and vertical GRF increased significantly when the foot rotated externally. Significant differences were observed in valgus-varus rotation torque and internal-external rotation torque of the knee joint under the two distance lunges and two foot position lunges (P < 0.05).No significant difference was found in knee muscle activation during the two distance lunges and during the two foot position lunges. High knee torque and compressive loadings with increasing lunge distance may cause knee injuries in badminton. When lunging in the external foot rotation under the maximum distance, high quadriceps force and posterior tibia translation force could result in knee injuries among badminton players.